Effect of additives on the orientation of magnetic Sr-ferrite powders in powder injection molded compacts - Cho, TS; Jeung, WY (POLYMER SOC KOREA, 2001)
The effect of additives on the orientation of magnetic Sr-ferrite powders has been studied during powder injection molding under applied magnetic field for fabricating multi-pole anisotropic sintered Sr-ferrite magnets. The orientation of the Sr-ferrite powders depends sensitively on the fluidity of powder-binder mixture, related to the binder additives and the injection molding temperature, and the magnetic field intensity. The orientation of Sr-ferrite powders is good for the compacts with stearic acid added in the binder system of paraffin wax/carnauba wax/HDPE, but it is poor for the compacts with silane coupling agent added. The orientation of Sr-ferrites higher than 80% is achieved at the following useful conditions; apparent viscosity lower than 2500 poise in 1000 sec(-1) shear rate and applied magnetic field higher than 4 kOe.
Keywords: MECHANICAL-PROPERTIES; COUPLING AGENTS